2017
DOI: 10.1016/j.cbi.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Aldose reductase (AKR1B) deficiency promotes phagocytosis in bone marrow derived mouse macrophages

Abstract: Macrophages are critical drivers of the immune response during infection and inflammation. The pathogenesis of several inflammatory conditions, such as diabetes, cancer and sepsis has been linked with aldose reductase (AR), a member of the aldo-keto reductase (AKR) superfamily. However, the role of AR in the early stages of innate immunity such as phagocytosis remains unclear. In this study, we examined the role of AR in regulating the growth and the phagocytic activity of bone marrow-derived mouse macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…36,37 Singh et al demonstrated that the inhibition of AR promoted the phagocytic activity of bone marrow-derived mouse macrophages via increased glycolysis and elevated levels of ATP and NADPH. 25 Our experiments showed that engeletin suppressed AR activity and enhanced the phagocytosis of RAW 264.7 macrophages, which is consistent with the previous studies. However, whether engeletin promotes phagocytosis via the same mechanism is not clear and requires further research.…”
Section: ■ Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…36,37 Singh et al demonstrated that the inhibition of AR promoted the phagocytic activity of bone marrow-derived mouse macrophages via increased glycolysis and elevated levels of ATP and NADPH. 25 Our experiments showed that engeletin suppressed AR activity and enhanced the phagocytosis of RAW 264.7 macrophages, which is consistent with the previous studies. However, whether engeletin promotes phagocytosis via the same mechanism is not clear and requires further research.…”
Section: ■ Discussionsupporting
confidence: 93%
“…Engeletin Promoted Phagocytosis in RAW 264.7 Macrophages. Because previous studies showed that AR deficiency promoted phagocytosis in mouse macrophages, 25 we used the neutral red assay and fluorescence microscopy to determine the effects of engeletin on the phagocytosis of RAW 264.7 macrophages. The neutral red assay demonstrated that engeletin treatment significantly increased the phagocytic activity in cells without LPS exposure, which suggests that engeletin enhances the phagocytic activity of cells at a basal level.…”
Section: ■ Resultsmentioning
confidence: 99%
“…AGE formation can lead to an imbalance in growth factors and inflammation imbalances in the ocular compartment of diabetic patients ( Obrosova and Kador, 2011 ). Further, upregulation of polyol via the hexosamine pathway is also associated with DR ( Sharma et al, 2005 ; Kowluru and Chan, 2007 ; Safi et al, 2014 ; Singh et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the AKR1B1 monomer and dimer were more highly expressed on Day 16 of pregnancy (Figure ). As a member of the aldo‐keto reductase superfamily, aldose reductase (AKR1B) inhibits macrophage phagocytosis in the bone marrow‐derived mouse macrophages (Singh, Kapoor, Mccracken, Hill, & Bhatnagar, ), and macrophages are crucial drivers of the immune response during infection and inflammation. IFNT can block the uterine development of the luteolytic mechanism but does not inhibit the production of PGF2α during pregnancy.…”
Section: Discussionmentioning
confidence: 99%